Performance Analysis of Quicksort Algorithm: An Experimental Study of Its variants - Dr shorman (International Journal of Advanced Science and Computer Applications, 2026)
The Quicksort algorithm is often the best practice choice for sorting due to its remarkable efficiency on average cases, small constant factors hidden in the θ(n log n) notation, and its in-place sorting nature. This paper provides a comprehensive study and empirical results of the Quicksort algorithm and its variants. The study encompasses all Quicksort variants from 1961 to the present. Additionally, the paper compares the performance of different versions of Quicksort in terms of running time on integer arrays that are sorted, reversed, and randomly generated. Our work will be invaluable to anyone interested in studying and understanding the Quicksort algorithm and its various versions.